Keratoconjunctivitis and corneal ulceration in a patient with erosive lichen planus - Arooba, Zahra; Batool, Anam; Asghar, Faizaan (Journal of the Pakistan Medical Association, 2025)
Lichen planus (LP) is an immune mediated mucocutaneous disease with a broad clinical spectrum, primarily affecting the but skin and oral cavity. Erosive lichen planus (ELP) is a rare variant of LP that manifests as erosions in the oral cavity as well as chronic erosions of the soles accompanied with severe disabling pain. Ocular LP is very uncommon presenting usually as keratoconjunctivitis and if left untreated can lead to vision impairment. We report the case of a woman who presented with characteristic skin lesions of lichen planus, accompanied by severe erosive oral and plantar lesions as well as bilateral keratoconjunctivitis and corneal ulceration. Key words: Lichen planus, erosive LP, ocular LP, keratoconjunctivitis.